Test about the Epistemological Obstacles presents in methodological strategies in Chemistry Teaching, a bibliography review (Research, Society and Development, 2019)
This article is characterized by a bibliographical review regarding the elements for the understanding of the epistemological obstacles proposed by Gaston de Bachelard, which originates from Physics, but analyzed from the Teaching of Chemistry. This research seeks to point out some relevant aspects regarding the use of methodological strategies used by professors of Chemistry in an attempt to facilitate the content, but that when not well used can create impediments in the learning of scientific knowledge. Thus, the research establishes registered references in the academic productions about these obstacles that are usually identified in the development of the acquisition of knowledge of Chemistry in the classroom.